2017
DOI: 10.3892/ol.2017.6704
|View full text |Cite
|
Sign up to set email alerts
|

RecQ helicase BLM regulates prostate cancer cell proliferation and apoptosis

Abstract: Prostate cancer (PCa) is a common malignant tumor and the second leading cause of morbidity and mortality in men worldwide. Considering the prevalence and effects of PCa in males, an understanding of the molecular mechanisms underlying PCa tumorigenesis are essential and may provide novel therapeutic strategies for treating PCa. Bloom syndrome protein (BLM) is a member of the RecQ helicase family. The major function of BLM is to uncoil the double-stranded DNA structure. It has previously been demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…BLM is overexpressed in some tumor cells, and abnormalities in BLM are associated with genome instability, which has been shown in recent studies to lead to tumorigenesis 1113. Recently, Qian et al showed that BLM was overexpressed in prostate cancer cells and tissue compared with benign prostatic hyperplasia cells and nonprostate cancer tissue 37. In 2015, Arora et al showed that in breast cancer, overexpression of BLM mRNA was significantly correlated with increased histopathological grade, larger tumors, ER-negative tumors, PR-negative tumors, and triple-negative tumor phenotypes, and associated with reduced BCSS 38.…”
Section: Discussionmentioning
confidence: 99%
“…BLM is overexpressed in some tumor cells, and abnormalities in BLM are associated with genome instability, which has been shown in recent studies to lead to tumorigenesis 1113. Recently, Qian et al showed that BLM was overexpressed in prostate cancer cells and tissue compared with benign prostatic hyperplasia cells and nonprostate cancer tissue 37. In 2015, Arora et al showed that in breast cancer, overexpression of BLM mRNA was significantly correlated with increased histopathological grade, larger tumors, ER-negative tumors, PR-negative tumors, and triple-negative tumor phenotypes, and associated with reduced BCSS 38.…”
Section: Discussionmentioning
confidence: 99%
“…From the pathway and interaction network analyses, we inferred that BRCA2 and BRCA1 have a majority of interacting partners that are largely associated with either DNA repair genes or helicases, viz., KRIT1, CTNS, USH2A, HEXB, MCCC1, MYO15A, CAPN3, GNPTAB, RHAG, PRLR, OTOF, GJB6, MCM8, CYP1B1, PRICKLE1, TP53, COL6A1, DNAAF1, SCN9A, CYP11B2, ATP6V0A2, NF1, ADA, MT-CYB, OPA1, ANG, HBB, MRE11 ( Figure 2B ). Notable among them is RecQ/BLM helicase, which has been recently reported to regulate cancer cell proliferation ( Qian et al, 2017 ). In the recent past, recommendations demonstrated the role of prostate serum antigen (PSA) levels correlating the patient’s race, age, and prostate volume ( Wu et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, conventional drugs such as cis-platinum and mitomycin are usually selected for use as auxiliaries in chemotherapy or radiotherapy for prostate carcinoma treatment (2,3). Several studies have directly or indirectly implied that patients with terminal cancer could be treated in the future using drugs targeting critical endogenous factors such as Her2/Neu, epidermal growth factor or tumor necrosis factor-α (25). Improved target selection of anti-cancer drugs is very important for clinical research.…”
Section: Introductionmentioning
confidence: 99%
“…BLM gene defects can cause Bloom syndrome, accompanied by cancer predisposition (69). A recent study indicated that knockdown of BLM impairs the normal proliferation and metabolism of cancer cells (5). Drugs targeting BLM have been used to treat cancer (5,1014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation